Application of Radiocraniometry in Anthropological Investigations - Zaborowski, Zbigniew; Piontek, Janusz (Anthropological Review, 1977)
The authors are addressing issues related to the technique of taking X-ray pictures of the skull, with a specific focus on the extent to which the skull is deformed in the picture compared to its actual form and dimensions. They propose a set of radiocraniometric points, defined to provide measurements comparable to those used in traditional craniometry. The methods for estimating cranial capacity from X-ray pictures are also discussed.